Short- and intermediate-term results of balloon aortic valvuloplasty and surgical aortic valvotomy in neonates. (24th February 2020) - Zaban, Nicholas B.; Herrmann, Jeremy L.; Hoyer, Mark H.; Brown, John W.; Alexy, Ryan D.
Abstract: Background: Balloon aortic valvuloplasty and open surgical valvotomy are procedures to treat neonatal aortic stenosis, and there is controversy as to which method has superior outcomes. Methods: We reviewed the records of patients at our institution since 2000 who had a balloon aortic valvuloplasty or surgical valvotomy via an open commissurotomy prior to 2 months of age. Results: Forty patients had balloon aortic valvuloplasty and 15 patients had surgical valvotomy via an open commissurotomy. There was no difference in post-procedure mean gradient by transthoracic echocardiogram, which were 25.8 mmHg for balloon aortic valvuloplasty and 26.2 mmHg for surgical valvotomy, p = 0.87. Post-procedure, 15% of balloon aortic valvuloplasty patients had moderate aortic insufficiency and 2.5% of patients had severe aortic insufficiency, while no surgical valvotomy patients had moderate or severe aortic insufficiency. The average number of post-procedure hospital days was 14.2 for balloon aortic valvuloplasty and 19.8 for surgical valvotomy (p = 0.52). Freedom from re-intervention was 69% for balloon aortic valvuloplasty and 67% for surgical valvotomy at 1 year, and 43% for balloon aortic valvuloplasty and 67% for surgical valvotomy at 5 years (p = 0.60). Conclusions: Balloon aortic valvuloplasty and surgical valvotomy provide similar short-term reduction in valve gradient. Balloon aortic valvuloplasty has a slightly shorter but not statistically significant hospital stay. Freedom from re-intervention is similar at 1 year. At 5 years, it is slightly higher in surgical valvotomy, though not statistically different. Balloon aortic valvuloplasty had a higher incidence of significant aortic insufficiency. Long-term comparisons cannot be made given the lack of long-term follow-up with surgical valvotomy.